Teater som danning i helseprofesjonene - Sæther, Wigdis; Sørbø, Jan; Gjengedal, Eva; Lykkeslet, Else (Nordisk tidsskrift for helseforskning, 2016)
Theater as `bildung` in the health professionsHealthcare workers who watch a theatre play about dementia, gain experiential knowledge about living with dementia. In this essay we discuss the nature of this knowledge in light of the concept of bildung. This discussion hinges on the Gadamers explication of the close ties between understanding (verstehen) and bildung. Theatre as an art form can yield insights into narratives of otherness and may trigger reflection of one’s own experiences and thus, provide opportunities for bildung.
Keywords: Bildung; theater; esthetic experience; life histories; professionality; danning/dannelse; teater; estetisk erfaring; livshistorie; profesjonalitet